1972
DOI: 10.1088/0031-9155/17/2/003
|View full text |Cite
|
Sign up to set email alerts
|

The emission spectrum of LiF (TLD-100) at low and high exposures

Abstract: The emission spectrum of LiF (TLD-100) was studied for high and low exposures. The ratio of the thermoluminescence of the high exposure (3.4 x IO4 R ) to that of the low exposure (100 R) was the same for all wavelengths. A tendency for the emission spectrum to shift to shorter wavelengths with higher temperature glow peaks was observed. The results are consistent with those of most other investigators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1974
1974
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…3 ) ; the smallest variations we were able to detect were about 5 nm. No effect from high doses was noticed up to 2 Mrad; this was experimentally proved by DeWerd and Stoebe (1972) and our results agree. Other colour film was successfully tested; the only shortcoming of our method is a lower sensitivity in the ultraviolet as well as in the blue region.…”
supporting
confidence: 87%
“…3 ) ; the smallest variations we were able to detect were about 5 nm. No effect from high doses was noticed up to 2 Mrad; this was experimentally proved by DeWerd and Stoebe (1972) and our results agree. Other colour film was successfully tested; the only shortcoming of our method is a lower sensitivity in the ultraviolet as well as in the blue region.…”
supporting
confidence: 87%
“…There is extensive evidence illustrating the dependence of supralinearity on impurity composition in LiF and other TL materials. Jasinska et a1 (1969) described LiF:Cu,Ag with f ( D ) = 1 up to lo3 Gy and DeWerd and Stoebe (1971) showed that the incorporation of OH-radicals can eliminate supralinearity in LiF-TLD. At the other extreme, Burgkhardt et a1 (1978b) describe a LiF:Na,Mg TLD with f(D),,,=6…”
Section: Dependence Of F(d) On Impurity Compositionmentioning
confidence: 99%
“…The main peak, which is used for dosimetry, occurs at about 200 "C and is numbered + Present address: Health Physics Division, Bhabha Atomic Research Centre, Bombay, India, 0022-3727/86/091791 + 17 $02.50 @ 1986 The Institute of Physics 5 , almost universally. The main emission from all the peaks is a broad band with a maximum at -420 nm (Dewerd and Stoebe 1972). However, some variations (Fairchild eta1 1978, Townsend etal 1983 and additional bands have been observed in the emission spectrum (Crittenden er a1 1974a, Wintersgill etal 1977.…”
Section: Introductionmentioning
confidence: 95%